2008
DOI: 10.1021/jp8034314
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Changes in the High-Frequency Dynamics of Mixtures by Dielectric Spectroscopy

Abstract: Additives to polymeric materials can lead to appreciable changes in the rates of relaxation and reaction in these mixtures that can profoundly alter material properties and function. We develop a general theoretical framework for quantifying changes in the "high-frequency" relaxation dynamics of mixtures based on classical transition state theory, in conjunction with mathematical statements regarding the dependence of the entropy (S+) and enthalpy (E+) of activation of the high-frequency relaxation time on dil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(91 citation statements)
references
References 86 publications
7
82
0
Order By: Relevance
“…This unusual type of kinetics has been observed in materials characterized by complex energy landscapes (50)(51)(52)(53), and negative activation parameters are observed in zeolite materials where confinement is very strong (54,55). The enthalpy-entropy compensation temperature, T comp (the slope of the linear relation) for the nanocomposites and thin films, is close to the estimated VFT temperature T 0 of their pure systems, as found in previous experimental studies of β-relaxation in GF liquids (56)(57)(58). Our data reduction in terms of the scale of collective motion is equally as compelling as the relation indicated above between τ and hu 2 i.…”
Section: Resultssupporting
confidence: 86%
“…This unusual type of kinetics has been observed in materials characterized by complex energy landscapes (50)(51)(52)(53), and negative activation parameters are observed in zeolite materials where confinement is very strong (54,55). The enthalpy-entropy compensation temperature, T comp (the slope of the linear relation) for the nanocomposites and thin films, is close to the estimated VFT temperature T 0 of their pure systems, as found in previous experimental studies of β-relaxation in GF liquids (56)(57)(58). Our data reduction in terms of the scale of collective motion is equally as compelling as the relation indicated above between τ and hu 2 i.…”
Section: Resultssupporting
confidence: 86%
“…For example, Chang et al [84] reported that adding small amounts of an antiplasticizer (sorbitol or water) to sucrose-antibody formulations resulted in a monotonic decrease in T g and τ α , but optimal stabilization was obtained at intermediate levels of added sorbitol or water. In these experiments, τβitalicJG changed with antiplastizer [86] in the same non-monotonic way as did stability, suggesting that these faster dynamic processes may be coupled directly to degradation rates.…”
Section: Dynamic Considerationsmentioning
confidence: 76%
“…The list of proposals considered hereafter does not try to be exhaustive, but only illustrative of the complexity of the problem analysed. Other plausible theoretical approximations have already been published by other authors [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 95%